Seismic Analysis of Concrete Buttress Dam Considering Intake Tower and Reservoir - Ali Mahdian Khalili; Bahram Navayi Neya (Journal of Rehabilitation in Civil Engineering)
This study evaluates the intake tower's effect on the buttress dam responses, considering the access bridge and reservoir under seismic loading in ANSYS using the finite element model. Wimbleball dam in England is assigned as a case study to assess the effects of different characteristics of the system components on seismic responses. Some parameters were applied, such as the presence of the intake tower and access bridge, reservoir water level, intake tower height, and internal water level. Nine cases with and without intake towers and access bridges have been studied by raising the reservoir water level, intake tower height, and internal water level, resulting in three-dimensional seismic analyses. Circular frequencies, crest displacements, and heel stresses of the dam have been presented for current cases. The interaction between the reservoir, dam, and intake tower can alter the case's stiffness and consequently change its frequencies. The modal analysis responses presented that the case's frequencies were reduced by raising the reservoir water level by up to 40% and increasing the intake tower height by up to 19%. The seismic results show that the heel stresses of the middle buttress increase by raising the reservoir water level by up to 39%. For constant water levels in the reservoir and tower, displacements and stresses of the middle buttress increased by increasing the intake tower height by up to 3% and 43%, respectively.